Towards real-time simulation of turbulent air flow over a resolved urban canopy using the cumulant lattice Boltzmann method on a GPGPU. Issue 189 (June 2019) - Lenz, Stephan; Schönherr, Martin; Geier, Martin; Krafczyk, Manfred; Pasquali, Andrea; Christen, Andreas; Giometto, Marco
Abstract: This work explores the feasibility of real-time large-eddy simulations of flow over urban canopies at the neighborhood scale. The cumulant lattice Boltzmann method is employed using a single General Purpose Graphic Processing Unit (GPGPU). In order to demonstrate the validity and efficiency of this approach we simulate wind flow in a neighborhood of Basel. Simulation results are validated against measurements from the Basel Urban Boundary Layer Experiment (BUBBLE) and are compared to previous CFD simulations. Turbulence statistics are found to be in agreement with corresponding tower measurements according to several validation metrics. While quantitative comparisons are limited to the six measurement locations of the field measurements, the available data supports the conjecture that real-time simulation of urban air flow is feasible at the neighborhood scale with the proposed numerical technique. Highlights: LES of urban air flow of a neighborhood of Basel, Switzerland. Simulation results are validated against tower measurements. First application of cumulant LBM with quartic parametrization to real world problem. It is shown, that LBM on GPGPUs can offer real-time simulations for urban air flows.